Analysis of Dynamic Effects During Forging of a Polygonal Disc Under Vibrating Conditions. (2015) - Nagar, Sumit; Kumar, Surender; Kumar, Aneesh
Abstract: Experiments have been conducted at various tribological conditions to study the deformation characteristics such as strain rate distribution, barrelling profile and processing load during forging of mild steel specimens at room temperature. On the basis of experimental results obtained, velocity field model and interfacial friction law have been constructed and energy solution have been developed for the calculation of forging load and dynamic effects of forging. Results so obtained have been presented graphically for a polygonal disc.